2013
DOI: 10.1007/s10616-013-9675-y
|View full text |Cite
|
Sign up to set email alerts
|

Genotoxicity of drinking water disinfection by-products (bromoform and chloroform) by using both Allium anaphase-telophase and comet tests

Abstract: Genotoxic effects of bromoform and chloroform, disinfection by-products of the chlorination of drinking water, were examined by using mitotic index (MI), mitotic phase, chromosome aberrations (CAs) and comet assay on root meristematic cells of Allium cepa. Different concentrations of bromoform (25, 50, 75 and 100 μg/mL) and chloroform (25, 50, 100 and 200 μg/mL) were introduced to onion tuber roots. Distilled water was used as a negative control and methyl methansulfonate (MMS-10 μg/mL) as positive control. Al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 29 publications
0
10
0
Order By: Relevance
“…The chromosomal aberrations are classified under two sub-groups as the clastogenic aberrations (chromosomal break and chromatin bridge); and the physiological aberrations (c-mitosis, sticky, laggard). The anaphase bridges show structural chromosomal mutation and can occur during the translocation of chromatid exchange which is unequal because of the following reasons: presence of disentric chromosomes, replication enzymes that are not much active, breakage and fusion of chromosomes and chromatids [34]. After the treatments with Reactive Blue 19, and the Reactive Black 5, the property of sticky of the chromosomes was determined.…”
Section: Discussionmentioning
confidence: 99%
“…The chromosomal aberrations are classified under two sub-groups as the clastogenic aberrations (chromosomal break and chromatin bridge); and the physiological aberrations (c-mitosis, sticky, laggard). The anaphase bridges show structural chromosomal mutation and can occur during the translocation of chromatid exchange which is unequal because of the following reasons: presence of disentric chromosomes, replication enzymes that are not much active, breakage and fusion of chromosomes and chromatids [34]. After the treatments with Reactive Blue 19, and the Reactive Black 5, the property of sticky of the chromosomes was determined.…”
Section: Discussionmentioning
confidence: 99%
“…Their putative genotoxicity was recently demonstrated in Petunia grandiflora and Gaillardia grandiflora by comet assay, in a pioneer study of plant–plant association for phytoremediation involving the treatment of textile dyes (Watharkar and Jadhav, 2014 ). Recently, it was demonstrated that bromoform (which may occur during disinfection processes of water) and chloroform (>25 μg/mL) increased chromosome aberrations and DNA damages, this last one assessed by comet assay in A. cepa roots (Khallef et al, 2013 ). Also chlorobenzoic acids (CBAs) may be found in soils contaminated with polychlorinated biphenyls (PCBs), and have mutagenic and carcinogenic effects in animals.…”
Section: Organic Pollutantsmentioning
confidence: 99%
“…Several studies have suggested the genotoxic and mutagenic potential of some DBPs. ( Beddowes et al, 2003 , Du et al, 2013 , Honer et al, 1980 , Khallef et al, 2015 , Kogevinas et al, 2010 , Pals et al, 2013 , Pals et al, 2011 , Richardson et al, 2010 , Stayner et al, 2014 , Wang et al, 2014 , Yuan et al, 2005 ) Specifically, higher levels of biomarkers of genotoxicity such as changes in micronuclei (MN) and DNA damage (comet assay) in peripheral blood lymphocytes have been reported in relation to brominated THM concentrations (excluding chloroform) in exhaled breath. ( Kogevinas et al, 2010 ) Increased levels of markers of genotoxicity in maternal binucleated lymphocytes were also identified during the first and second trimester of pregnancy in relation to THM exposure from residential water ( Khallef et al, 2015 , Stayner et al, 2014 ) and swimming pool water( Honer et al, 1980 , Richardson et al, 2010 ).…”
Section: Introductionmentioning
confidence: 99%